Gene therapy for Leber congenital amaurosis. (2nd January 2018) - Kumaran, Neruban; Smith, Alexander J.; Michaelides, Michel; Ali, Robin; Bainbridge, James
ABSTRACT: Introduction : Leber congenital amaurosis (LCA) is a group of recessively inherited, early infantile-onset, severe rod-cone dystrophies that can result from defects in at least 25 genes, including RPE65, CEP290, RDH12, AIPL1 and GUCY2D . The possibility of benefit is offered by therapeutic intervention to provide the functional gene that is otherwise lacking. Areas covered : We searched PubMed for publications using the relevant keywords. Expert commentary : Clinical trials of gene therapy for LCA owing to defects in RPE65 have demonstrated benefit with improved function of rod photoreceptor cells. A gene therapy for this condition has been approved by the FDA. Ongoing clinical trials aim to determine whether cone photoreceptor cell function can be protected by appropriate gene delivery at an early stage of the disease. Clinical trials of gene therapy for LCA owing to defects in 5 other genes are planned.